The Past, Present and Future of Social Stratification from Said Nursi’s Perspective - Orhan, Sadettin (Journal of Muslims in Europe, 2024)
Social stratification is a common factor in almost every society on earth. Societies exhibit a certain hierarchical structure measured by either abstract or concrete criteria. With industrialisation, the form of stratification changed. The proletariat and the bourgeoisie formed the two main social strata of this new society. Studies aimed at understanding and explaining this change in the social structure have produced many texts with a rich theoretical discussion. In our study, the views on stratification put forward by Said Nursi, an Islamic scholar and commentator on the Qurʾan, are discussed. Nursi includes important determinations and evaluations of people, society and stratification in his works, which total more than six thousand pages. We hope that these findings and evaluations will contribute to disciplines, particularly sociology, that deal with stratification.